The effect of the problem-based learning model integrated with the ethnomathematics of the marble game on students’ mathematical problem-solving ability - afni, Syifa Husna Ramadhani; Ella Andhany (Desimal: Jurnal Matematika, 2025)
The current mathematics learning process still shows a lack of effectiveness, resulting in students’ low mathematical problem-solving abilities. This study aims to determine the effect of the Problem-Based Learning model integrated with the ethnomathematics of the marble game on students’ mathematical problem-solving skills. This quantitative research employed an experimental method. The results showed a significant effect of the PBL model integrated with the ethnomathematics of the marble game on students’ mathematical problem-solving abilities. The findings revealed that the PBL model integrated with the ethnomathematics of the marble game had a significant effect on the mathematical problem-solving abilities of eighth-grade students at MTs Negeri Batu Bara.